In Search of Transformative Ways of Being in Mission: Introducing the Mission Spirituality Spiral - Lepori, Laura (International bulletin of mission research, 2023)
This article reflects on the interface between missiology (and mission) and spirituality (including spirituality in practice). It explores the relationship between the two disciplines and introduces the mission spirituality spiral, which can be used both as an analytic and as a mobilizing tool. Mission and spirituality are explored at their core. Their cohesiveness and inseparability lead to the notion of mission spirituality, which takes shape in the mission spirituality spiral. The article explains the dimensions of the spiral, which flow one into the other and culminate in the discernment of transformative ways of being in mission.